PATH-14. Alteration of histopathological diagnoses by molecular profiling. (3rd June 2022) - Knirsch, Stephanie; Milde, Till; Pfister, Stefan M; Blattmann, Claudia
Abstract: Here, we present a 4.5 year old patient presented with disturbed vision (double vision) and nausea over 2 weeks. Cerebral MRI revealed a tumor mass (6.5 x 6 x 5cm) located in the left temporal lobe. A macroscopical complete resection was achieved in May 2020. Conventional histopathology diagnosed a glioblastoma multiforme WHO IV° locally as well upon central review. A pleomorphic xanthoastrocytoma was considered to be unlikley due to the lack of eosinophile granular corpuscules, CD34-positive cells and dense reticulin fibres. The patient received treatment according to the SIOP HGG protocol with a postsurgical radiotherapy (total dosage of 54 Gy) accompanied by oral chemotherapy with temozolomide and valproic acid. After completion of radiotherapy, another 12 cycles of oral temozolomide were applied resulting in 1 year of consolidation treatment. In parallel, the tumor tissue was examined molecularly through the INFORM precision oncology platform (INdividualized Therapy FOr Relapsed Malignancies in Childhood). The results revealed an NTRK1-fusion as possible treatment target. Furthermore, methylation profiling of the tumor classified it as a pleomorphic xanthoastocytoma. The molecular results were completed during treatment of the patient and were discussed interdisciplinary. Finally, the diagnosis was changed integrating histopathology and molecular results, but the treatment was completed. In about 10% of the brain tumor cases within molecular diagnostic studies such as INFORM or PTT, the histopathological diagnosis differs from the molecular results leading to reconsideration of the initial diagnosis and potential impact on clinical management. These results demonstrate the importance of molecular profiling in brain tumors (and sarcomas) to complement conventional histopathology and select appropriate risk adapted treatment, especially in young patients.